Developing and testing the feasibility of a theory-based brief counseling intervention to promote physical activity in breast cancer survivors enrolled in the PAC-WOMAN trial - Sofia Franco; Eliana V. Carraça; Inês Nobre; Bruno Rodrigues; Vítor Ilharco; Lea Kahlert; Marlene N. Silva (Pilot and Feasibility Studies)
Abstract Background Despite the benefits of physical activity (PA), cancer survivors report engagement barriers, and existing interventions often lack comprehensive solutions. Theory-based interventions using evidence-based behavior change techniques (BCTs) have been shown to be effective in promoting PA for breast cancer survivors, although their feasibility and acceptability lack evidence. The PAC-WOMAN trial is a three-arm randomized controlled trial aimed at promoting short- and long-term PA and improving the quality of life of breast cancer survivors. This study describes the development of a brief counseling theory-based motivational intervention from the PAC-WOMAN trial, assessing its feasibility and acceptability. Methods A broad search of theory-based interventions for people with chronic diseases was conducted. Key strategies from each intervention helped shape the main components and BCTs used in the eight bimonthly sessions of the PAC-WOMAN brief counseling intervention, which was based on self-determination theory principles and aimed at empowering participants to develop self-regulation resources for PA through basic psychological needs satisfaction. A toolkit and manuals for intervention facilitators and participants were developed. A feasibility study was conducted to monitor implementation fidelity, acceptability, adherence, and participants’ experiences (via a focus group). Results Twelve women (mean age 55.9 ± 6.7 years) participated. Implementation monitoring indicated that the intervention was feasible. The attrition rate was 25%. Focus-group discussion suggested that weekly sessions would increase attendance, highlighted the helpfulness of self-monitoring and the importance of role models for PA, and identified the session on safely exercising at home as key in improving PA levels. Conclusions This research aims to enhance systematic reporting in intervention development by detailing the specific BCTs used, translating them into implementation strategies, providing comprehensive resources for facilitators/participants, and supporting the implementation, dissemination, and adoption of a theory-based intervention informed by previous research. Feasibility testing suggests that the intervention was well accepted by participants and feasible, although it could benefit from adjustments in format to increase compliance. Trial registration NCT05860621, registered 20 April 2023 — retrospectively registered, https://clinicaltrials.gov/study/NCT05860621 . Registered 21 April 2023 — retrospectively registered, https://doi.org/10.17605/OSF.IO/ZAQ9N . UMIN000050945, registered 27 April 2023 — retrospectively registered, https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000058070 .